Balancing antimicrobial performance with hemocompatibility in amphiphilic homopolymers. Issue 21 (21st September 2018) - Zhu, Zhiyuan; Jeong, Gookyeong; Kim, Seung‐Jin; Gadwal, Ikhlas; Choe, Youngson; Bang, Joona; Oh, Min‐Kyu; Khan, Anzar; Rao, Jingyi
Abstract : This work establishes amphiphilic polymethacrylates as new antimicrobial candidates that can be synthesized through a combination of controlled free radical polymerization and sequential postpolymerization modification protocols. When conjugated with a polyethylene glycol segment, the block copolymers exhibit a balanced performance between high antibacterial activity and high hemocompatibility.